An investigation of the characteristics and function of the phosphorylation of proteins in synaptic vessels - Glaser, J.(Jonathan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Medical biochemistry)) - University of Stellenbosch, 1980.